2009
DOI: 10.1631/jzus.b0820273
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer, one entity or three

Abstract: Abstract:Understanding of the mechanism of colorectal carcinogenesis has been gaining momentum for some years on account of its high incidence and impact on the lives of individuals affected. Different genetic abnormalities have been found in colorectal cancers from different sites. For example, proximal colon cancer is usually related to the nucleotide instability pathway, as microsatellite instability (MSI). However, distal colon cancer is usually associated with specific chromosomal instability (CIN). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
166
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(178 citation statements)
references
References 67 publications
7
166
1
4
Order By: Relevance
“…Recent epidemiologic studies have reported a proximal migration of CRCs evidenced by increased incidence of right-sided colon cancers and a decrease in incidence of rectosigmoid tumors (2,3), suggestive of different risk factors associated with carcinogenesis in proximal and distal colon (4,5). These data support the concept originally proposed by Bufill in 1990 that cancers originating from these two different anatomical locations should have distinct molecular pathogenesis (6).…”
Section: Introductionsupporting
confidence: 76%
“…Recent epidemiologic studies have reported a proximal migration of CRCs evidenced by increased incidence of right-sided colon cancers and a decrease in incidence of rectosigmoid tumors (2,3), suggestive of different risk factors associated with carcinogenesis in proximal and distal colon (4,5). These data support the concept originally proposed by Bufill in 1990 that cancers originating from these two different anatomical locations should have distinct molecular pathogenesis (6).…”
Section: Introductionsupporting
confidence: 76%
“…However, rectal cancer differs from descending and sigmoid colon cancer in molecular features, treatment approaches, and prognosis. 50 , 51 Thus, we believe that it is more appropriate to apply the herein used definition on future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, etiological pathways underlying colon cancers proximal to the splenic flexure are different from those distal to the splenic flexure and evidence that risk factors for tumors originating from different colorectal subsites vary is accumulating. 14,15 The aim of this study was to assess the association of prediagnostic plasma concentrations and dietary intakes of carotenoids and vitamins A, C and E with the risk of colon and rectal cancer in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) study. In addition, analyses for colon cancer were stratified by subsite.…”
mentioning
confidence: 99%